Modelagem matemática no ensino das porcentagens. - Barbosa, Ivanira Galdino. (2012)
In order to investigate the advantages of modeling in teaching and learning of mathematics, we address the importance and benefits that this teaching method provides for a meaningful learning, and with the purpose of showing these advantages, we choose a theme related to the everyday. The work consists of applying a series of activities where we can compare the responses of two classes the first year of high school, classified as class A and class B. In group A, the activities were developed without the worry of using the proposed modeling. In group B, the same activity was developed primarily with the help of mathematical modeling. The research procedures used in this paper are based on conceptions of, and BIEMBENGUT HEIN, (2005), BIEMBENGUT, (2009), Barbosa (2001 and 2003), Burak, (2005), ISAIA, and BISOGNIN BISOGNIN, (2009) , which justifies the importance of this issue for the teaching and learning of mathematics. The results lead to the conclusion that the use of modeling provided the motivation and students' interaction in the classroom, in addition to providing greater understanding of concepts studied in the content of the proposed activities.